An evolutionary perspective on the emergence and implementation of mission-oriented innovation policy: the example of the change of the leitmotif from biotechnology to bioeconomy - Leonard Prochaska; Daniel Schiller (Review of Evolutionary Political Economy, 2021)
The design and implementation of innovation policy funding programmes has been the subject of scientific and political debate for decades. Especially the increasingly popular approach of mission-oriented innovation policies is a much discussed subject. The question of how missions arise, what rhetoric accompanies them and how they are eventually implemented has not yet been sufficiently clarified and specification is lacking. Whether mission-oriented innovation policy actually follows a strict top-down logic, or whether the policymaking process rather resembles a certain evolutionary scheme is questioned in this study. On the basis of the change within many policy strategy papers from biotechnology to a much broader bioeconomy, it is shown that, in reality, the transition does not follow a linear sequence. Neither excessive prioritisation nor neglect of a selected sector can be confirmed in this analysis. Within the bioeconomy, however, a clear change can be identified. Biotechnology funding was visibly reduced as part of the change of leitmotif while R&D increased in the agricultural sector in particular. Furthermore, it becomes clear that the issue of missing markets, which is predicted in theoretical studies, can also be confirmed empirically. So far, in terms of public involvement, little effort has been invested in the practical application of bioeconomical knowledge, which is why the intended transition towards bio-based economic activities is lagging behind expectations.
Keywords: H50; O38; O52; Q57; 320; Innovation policy; Policy design; Funding data; Biotechnology; Bioeconomy